Diffusion of Digital Payment System in Rural India (Global Journal of Management and Business Research, 2018)
Rural sector in India is home to 66% of the nation's populace which is currently 870 million individuals. Rural India has noteworthy effect on the financial advancement of the nation, and with the developing changes of ICT entrance, and users among rural regions will constitute about portion of all internet users in India in 2020. Considering the advantages like straightforwardness in exchanges, scope for diminishing parallel economy and enhancing the simplicity of business, it is exceptionally fundamental that the change towards digital payment, even in the rural economy is enabled. The present study revolves around digital payment systems in rural areas of South India. The intention of the research is to determine the benefits of digital payments and its influence on the rural sector of India. The study conducted convenient sampling survey with selected number of respondents in rural part of Southern India. The paper presents conceptual framework for better understanding of the concept and uses SEM as the research tool for obtaining Good Fit Model.
Keywords: digital payments; rural sector; economy